Acyl Carrier Protein 3 Is Involved in Oxidative Stress Response in Pseudomonas aeruginosa - Chen, Wei; Wang, Bo; Gruber, Jordon D.; Zhang, Yong-Mei; Davies, Christopher (Frontiers in Microbiology, 2018)
The human opportunistic pathogen Pseudomonas aeruginosa expresses three acyl carrier proteins (ACPs): AcpP, Acp1 and Acp3. The function of AcpP in membrane fatty acid synthesis was confirmed recently, but the physiological roles of Acp1 and Acp3 remain unclear. To address this, we investigated the physiological role of Acp3 in P. aeruginosa. We found that expression of Acp3 dramatically increases in the log phase of cell growth and that its transcription is under the control of the QS regulators LasR and RhlR. Deletion of acp3 from P. aeruginosa strain PAO1 results in thicker biofilm formation, increased resistance of the strain to hydrogen peroxide, and higher persistence in a mouse infection model. Tandem-affinity purification experiments revealed several novel protein-binding partners of Acp3, including KatA, the major catalase in P. aeruginosa. Acp3 was found to repress the catalase activity of KatA and, consistent with inhibition by Acp3, less reactive oxygen species are present in the acp3 deletion strain. Overall, our study reveals that Acp3 has a distinct function from that of the canonical AcpP and may be involved in the oxidative stress response.